Estrategias de organización gremial de mujeres trabajadoras de la construcción en La Paz y El Alto, Bolivia; Organizational strategies of unionized women construction workers in the cities of La Paz and El Alto, Bolivia - Magali Marega (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2020)
– In this article I analyze, from an anthropological perspective, the organizational strategies of female construction workers in the cities of La Paz and El Alto, Bolivia, collectivized through the Association of Women Builders (ASOMUC using its Spanish initials).After identifying some of the contextual dimensions that configure the development of organizational strategies linked to the way in which production is organized within the construction industry, I will explore from a historical perspective the organizing experiences of workers in this sector as well as the interventions of the state. In addition to patriarchal and racist structures, which permeate productive and reproductive spaces, I argue that female construction workers have typically prioritized a strategy of alliances with actors from civil society and the state thereby enabling them to exercise political influence, to make visible their labor demands and to establish themselves as political actors. The field work was carried out as an associate researcher in a research stay at the Instituto de Investigaciones Socio-Económicas de la Universidad Católica Boliviana, IISEC.
Keywords: Z13; Z18; P16; O54; N66; N36; L31; J81; J71; 330; Work; Organizational strategies; Women construction workers; Construction industry; Bolivia